2022
DOI: 10.1007/s10389-022-01728-w
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and attitudes towards Covid-19 vaccines: narratives from members of the UK public

Abstract: Aim The aim of the paper is to enhance understanding of how members of the public make sense of the Covid-19 vaccines and to understand the factors influencing their attitudes towards such artefacts of pandemic governance. Methods The paper draws on 23 online in-depth interviews with members of the UK public and builds on relevant literature to examine participants’ perceptions of the benefits and risks of Covid-19 vaccines, the sources that have shaped th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…From a clinical aspect, it has been shown that this vaccine doesn't affect performance and implantation in assisted reproductive cycles following vaccination [26,27]. However, despite those studies, low compliance to the vaccine peruse [10,[28][29][30]. The impetus for this study came about due to the persistent misinformation and rumors widely disseminated on social media about the effects of the BNT162b2 vaccine on women's fertility.…”
Section: Discussionmentioning
confidence: 95%
“…From a clinical aspect, it has been shown that this vaccine doesn't affect performance and implantation in assisted reproductive cycles following vaccination [26,27]. However, despite those studies, low compliance to the vaccine peruse [10,[28][29][30]. The impetus for this study came about due to the persistent misinformation and rumors widely disseminated on social media about the effects of the BNT162b2 vaccine on women's fertility.…”
Section: Discussionmentioning
confidence: 95%
“…Example questions include: "Cruise travel is too expensive" (financial risk); "Cruise travel is a waste of time" (time risk); "Political tension between my country and my preferred cruise destination makes me feel uncomfortable to take a cruise" (politics risk); "Taking a cruise is putting my health at risk" (health risk); "The language barrier is a problem with cruise travel" (cultural risk) (Reisinger & Mavondo, 2006). Two new variables (vaccine perceptions and protective behaviors) were developed based on health education research (Syan et al, 2021;Resnicow et al, 2021;Ajana, Engstler, Ismail, & Kousta, 2022). Example questions include "When the COVID-19 vaccine is ready, I would like to take the vaccine;" "Taking the COVID-19 vaccine before cruise travel is necessary for me" (vaccine perceptions) and "Using hand sanitizer that contains at least 75% alcohol;" "Social distancing, keeping about 6 feet between yourself and other people" (protective behaviors).…”
Section: Measurementmentioning
confidence: 99%
“…The focus of the study was on exploring participants' understandings of and attitudes toward COVID-19 vaccines and vaccination passports as well as the factors, such as risk perceptions, influencing these. This article presents the findings pertinent to the vaccine passports, whereas findings pertinent to the vaccines are presented in another article (Ajana et al, 2022). At the time of conducting the interviews, COVID-19 vaccine passports were in the initial state of being introduced in the United Kingdom.…”
Section: Study Detailsmentioning
confidence: 99%